Hospital Financial Resilience Model Based on Resource-Based View and Dynamic Capabilities - Yosefina Andia Dekrita; Imanuel Wellem; Paulus Libu Lamawitak (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to develop and examine a Hospital Financial Resilience model based on the Resource-Based View (RBV) and Dynamic Capabilities (DC) within healthcare organizations. Design/methodology/approach – This study employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to hospital leaders and managers involved in financial and operational management. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among the research variables. Finding/Results – The results show that Resource-Based View has a positive and significant effect on Hospital Financial Resilience, indicating that the management of valuable, rare, inimitable, and non-substitutable resources strengthens financial resilience. Dynamic Capabilities also positively and significantly influence financial resilience through the organization’s ability to sense opportunities, seize strategic actions, and reconfigure resources in response to environmental changes. Originality/Value – This study provides theoretical and practical contributions by presenting an integrated Hospital Financial Resilience model based on RBV and DC. The model offers strategic guidance for hospital management in improving financial sustainability and ensuring the continuity of healthcare services amid environmental uncertainty.